Investigation and development of modified ross yoke mechanism on alpha-parallel-cylinder stirling engine - Kwankaomeng, Sutapat (My University, 2018)
This paper presents the redesign and modification of a Ross yoke mechanism driving an alpha Stirling engine with parallel cylinder arrangement. Engine sealing is a crucial factor affecting engine operation, power, and maintenance. Friction and lateral force acting on piston seals induce major wear and finally lead to leakage and losses in both power and operating cost. To reduce these problems, linear reciprocating and balancing motion of both piston and connecting rod are preferred. Mechanical inversion is introduced to invert general motion of connecting rod to rectilinear translation. The original Ross yoke part is altered from pin joints to slot pin joints allowing piston rod to be driven straight. Length of the slot groove was adjusted and optimized. Motion of the modified Ross yoke was investigated theoretically and experimentally. Both analytical model and prototype have the same operating conditions and swept volume of 25 cm3. The ambient air was used as the working gas which was heated by LPG at flow rate of 0.6 kg/h and cooled by water. The maximum speed of 977 rpm was attained. Recorded maximum power and torque were 0.549 W at 486 rpm and 0.014 Nm at 260 rpm, respectively. The modified Ross yoke Stirling engine has operated smoothly when its piston rods were redesigned to slide linearly.
Keywords: Alpha-type; Ross yoke; Stirling engine